O gênero Bauhinia L. na região de Bauru e seus metabólitos secundários: contribuições para estudos de plantas medicinais - Leite, Monica Regina Vieira [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The history of plants and human beings has been connected since the beginning. Today, with the domestication of plants, both have created this relationship of interdependence, and man has the task of exploring nature according to his needs and in the most sustainable way possible. The use of medicinal plants is something that has always been present in society, both in the folk medicine and in the scientific medicine. Scientific studies of such plants have provided an advance in the development of herbal medicines, improved the knowledge regarding their medicinal properties and the best natural conditions to exploit them. For this paper, a bibliographical revision of the genus Bauhinia L. and its contributions in the pharmacological area as object of research, giving focus on the species that occur in the region of Bauru was chosen. Bauhinia is composed by species with very high medicinal value because it has several classes of compounds such as flavonoids, terpenoids, tannins, alkaloids and quinones, for example. Studies have demonstrated antioxidant, antimicrobial, anti-inflammatory, hypoglycemic, antitumoral activities, among others. In Bauru, a region of Semideciduous Seasonal Forest and Cerrado vegetation, three species of Bauhinia have already been recorded: B. longifolia (Bong.) Steud., B. ungulata L, B. holophylla (Bong.) Steud. Although there are few published papers, B. longifolia, has antiviral activity and a high antioxidant potential, it has in its constitution flavonoid glycoside derivatives from myricetin, kaempferol and quercetin. Bauhinia ungulata, popularly used in the treatment of diabetes, exerts antimicrobial and antioxidant activity, besides presenting exclusive compounds in its constitution, like quercetin-3-O-arabinofuranoside, harmane and eleagnine. Bauhinia holophylla has been increasingly studied mainly because of its hypoglycemic activity... (Complete abstract electronic access below)

A história das plantas e dos seres humanos está conectada desde seus primórdios. Hoje, ainda mais! Após a domesticação das plantas, ambos criaram uma relação de interdependência, cabendo ao homem a tarefa de explorar a natureza de acordo com suas necessidades e da forma mais sustentável possível. O uso de plantas medicinais é algo que sempre esteve presente na sociedade, tanto na medicina popular quanto na medicina científica. Os estudos científicos referentes a tais plantas proporcionaram um avanço na produção de fitoterápicos, aprimoraram o conhecimento em relação às suas propriedades medicinais e as melhores condições naturais para explorá-las. Para o presente trabalho optou-se por uma revisão bibliográfica do gênero Bauhinia L. e suas contribuições na área farmacológica como objeto de pesquisa, dando foco nas espécies que ocorrem na região de Bauru. Bauhinia é composto por espécies com alto valor medicinal por possuir diversas classes de compostos como flavonoides, terpenoides, taninos, alcaloides e quinonas por exemplo. Estudos demonstraram atividades antioxidante, antimicrobiana, anti-inflamatoria, hipoglicemiante, antitumoral, entre outras. Em Bauru, região onde ocorre a Floresta Estacional Semidecidual e Cerrado, já foram registradas três espécies de Bauhinia: B. longifolia (Bong.) Steud., B. ungulata L., B. holophylla (Bong.) Steud. Embora haja poucos trabalhos publicados, B. longifolia apresenta atividade antiviral e um alto potencial antioxidante, possui em sua constituição heterosídeos de flavonoides derivados de miricetina, kaempferol e quercetina. Bauhinia ungulata, utilizada popularmente no tratamento contra o diabetes, exerce atividade antimicrobiana e antioxidante, além de apresentar em sua constituição compostos exclusivos como quercetina-3-O-arabinofuranosídeo, harmano e eleagnina... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Medicina alternativa; Plantas dos cerrados; Cerrados; Fitoterapia; Pata de vaca; Alternative medicine